A INSERÇÃO DA ESTRATIFICAÇÃO DE RISCO NA PUERICULTURA PARA O MANEJO ADEQUADO DE CRIANÇAS MENORES DE DOIS ANOS - LIMA, Graciara Leticia Bezerra (2024)
Introduction: Considering the importance of comprehensive care for children, the Statute of Children and Adolescents and the National Policy for Comprehensive Child Health Care (PNAISC) within the scope of the Unified Health System (SUS), the health team can and should organize the work process in order to offer equal and comprehensive care to children, using the criteria of family context, individual needs and risk factors from a systematic, integrative and comprehensive perspective. Objective: To evaluate the inclusion of risk stratification in childcare regarding the organization of work processes in the appropriate management of children under two years of age and in infant mortality. Methods: The research was developed using the descriptive, cross-sectional and observational quantitative method, carried out through the collection of primary data through a data extraction form and a child risk stratification instrument. Results: In 139 medical records of children included in the study, it was possible to analyze the insertion of risk stratification in childcare both in the organization of work processes in the adequate management of children under two years of age, and in infant mortality of children under one year of age. We observed adequate sharing of care (reference and counter-reference), a reduction in errors and the promotion of best practices, that the health team developed a more sensitive view with the target population in the identification of medium and highrisk children, that factors such as problems during pregnancy and/or childbirth, birth weight classification, APGAR classification and alteration of screenings had statistical significance for high risk and the reduction of the mortality rate in children under one year of age in the city of Caxias. Final Considerations: The main objective of risk stratification was achieved, which is the continuous monitoring of the child's growth and development, enabling the early identification of situations that represent a risk of illness, worsening or death and the appropriate direction for the necessary preventive or care interventions. Since it allowed the structuring of work processes, the timely management of high-risk children and the control of infant mortality, it raised awareness of qualified professional practice, encouraged greater adherence of the population to childcare and the connection to the team and the health unit.